WACANA BERITA KEKERASAN SANTRI PONDOK PESANTREN GONTOR DI REPUBLIKA ONLINE - Ridha, Nisrina Salsabila; Anwari (Universitas Hasyim Asy'ari, 2023)
In every online media platform, there exists a diverse range of ideologies and perspectives that influence the production of news content. Republika Online adheres to its own distinct ideology in the dissemination of information to the publik. Ideology can be discerned by analyzing the textual structure and discourse employed by each media platform. In the year 2022, a significant number of acts of violence occurred within the realm of education. Among these incidents was a case of violence against students at Gontor Islamic Boarding School, located in Ponorogo, East Java. Acts of violence can have adverse effects on both physical and mental health. In the case of the violence that occurred at Gontor Islamic Boarding School, it tragically resulted in the fatality of one of the students, highlighting the severe consequences of such incidents. This thesis focuses on two research questions: Firstly, how does Republika Online, as an online media platform, employ textual structure in presenting news regarding the violence against students at Gontor Islamic Boarding School, specifically in the edition from 06 to 08 September 2022. Furthermore, this study aims to investigate the discourse employed by Republika Online, an online media platform, in presenting news regarding the violence against students at Gontor Islamic Boarding School in the edition from 06 to 08 September 2022. In order to address these two issues, the researcher employed a qualitative (non-participant) approach. In this research, the researcher utilized Teun A. Van Dijk's discourse analysis method to analyze the